Prevalence and correlates of intimate partner violence against women: results from Mozambique Demographic and Health Survey 2022–2023 - Shaikh, Masood Ali (Frontiers in Public Health, 2025)
BackgroundIntimate partner violence (IPV) is a widespread public health problem that affects women worldwide and represents a significant violation of human rights.MethodsThis study utilized deidentified data from the 2022–2023 Mozambique Demographic and Health Survey to conduct a secondary analysis on the lifetime prevalence of IPV perpetrated by their current or most recent husband/intimate partner, and its associated factors. The analysis focused on 12 experiential, attitudinal, and socio-demographic attributes in women aged 15–49. For bivariate analysis, simple binary logistic regression models were used to identify correlates at the cutoff level of ≤0.20 p-value, which were then incorporated into the multivariable binary logistic regression model to analyze their associations with IPV. Model fit and collinearity were assessed to determine the utility of the multivariable analysis.ResultsAltogether, 32.65% of women surveyed reported having experienced emotional, physical, or sexual violence from their current or most recent husband (for ever-married women) or intimate partner (for never-married women). Emotional IPV was the most common form, affecting 22.40% of respondents, closely followed by physical IPV at 21.34%. Women’s involvement in decision-making, their partner’s use of alcohol and controlling behavior, and knowledge of their father having ever beaten their mother were found to be statistically significantly associated with IPV in the multivariable model.ConclusionIPV is shaped by a multitude of complex factors. One out of three women reported having experienced IPV, stressing the need for effective public health and societal measures to address and eradicate IPV in Mozambique.